1990
DOI: 10.1182/blood.v76.4.849.849
|View full text |Cite
|
Sign up to set email alerts
|

The expression of IgG allotypes on platelets and immunization to IgG allotypes in multitransfused thrombocytopenic patients

Abstract: We investigated whether the platelet-membrane surface carries IgG allotypic antigens and whether these determinants may be important in platelet transfusion therapy. Using a hemagglutination inhibition assay, we showed that the G1 m IgG allotypes (a. x, f) and K1 m and K3m light-chain allotypes are expressed on the surface of platelets, whereas G3m allotype antigenic determinants were not detectable. In 146 multitransfused thrombocytopenic patients, 35 (24%) patients were found to have antiallotypic antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…To our knowledge, there have as yet been no reports demonstrating whether the inhibitory FcγRIIB‐receptor is utilized by anti‐D, although in a mouse model of ITP, in contrast to IVIG, monoclonal RBC‐reactive antibodies [60] functioned independently of FcγRIIB expression [46]. This further supports the original notion of Cooper et al .…”
Section: Potential Mechanisms Of Action – Rh Immune Globulin (Anti‐d)supporting
confidence: 64%
See 1 more Smart Citation
“…To our knowledge, there have as yet been no reports demonstrating whether the inhibitory FcγRIIB‐receptor is utilized by anti‐D, although in a mouse model of ITP, in contrast to IVIG, monoclonal RBC‐reactive antibodies [60] functioned independently of FcγRIIB expression [46]. This further supports the original notion of Cooper et al .…”
Section: Potential Mechanisms Of Action – Rh Immune Globulin (Anti‐d)supporting
confidence: 64%
“…FcR‐independent mechanisms of action of IVIG have been reported in diseases other than ITP and these deserve mention as they may be also active in patients with ITP. For example, in contrast to the recognized efficacy of IVIG therapy in ITP and platelet‐specific (human platelet antigen; HPA1a) alloimmune disorders [4–6,45], most investigators have failed to document an effectiveness of IVIG in platelet human leucocyte antigen (HLA) alloimmune disorders [46]. This is intriguing because of the generally similar immunopathogenesis of platelet destruction in these different immune platelet disorders, that is, antibody‐opsonized platelet destruction via FcR‐mediated phagocytosis in the RES.…”
Section: Potential Mechanism Of Action – Intravenous Gammaglobulinmentioning
confidence: 99%
“…As part of the overall PK assessment, subjects were genotyped for the most common IgG1 GM alleles (GM3 and GM17) to determine if subject allotype impacts upon the activity of the VRC01 drug product. VRC01 contains the GM3 allele in the constant region of the heavy chain (γ1), and GM determinants of IgG1 have the potential to be immunogenic and anti‐allotype antibodies have been detected when individuals are exposed to an allotype they do not possess in their genome . No correlations to any of the PK or clinical parameters were seen based on subject GM allotyping; therefore, subject allotype, or the theoretical potential for an anti‐GM3 response, had no influence on PK, virus neutralization or safety outcomes in this study.…”
Section: Discussionmentioning
confidence: 70%
“…21, 22, 23 Pre-clinical studies in murine allo-HSCT models indicate that RBC transfusions can sensitize transplant recipients to minor histocompatibility antigens (miHA), 24, 25, 26 while clinical studies of platelet transfusion found platelet-specific and anti-human leukocyte antibodies in multiple platelet-transfused patients. 27, 28, 29 Thus, third-party transfusions might serve as a source of alloantigen that primes donor T cells, via indirect antigen presentation by donor-derived dendritic cells, to antigens mismatched between the stem cell donor and recipient, 25, 30 and contribute to increased risk of aGvHD. 31, 32, 33…”
Section: Introductionmentioning
confidence: 99%